Structural and functional insights into NAD(P)H-quinone oxidoreductases in lavender: implications for abiotic stress tolerance and essential oil production - Liu, Dafeng; Li, Na; Deng, Huashui; Song, Daoqi; Maimaiti, Minawaier; Nuerbieke, Ayidana; Yekepeng, Mingtai; Aili, Kailibinuer (Frontiers in Plant Science, 2025)
Lavender essential oils (EOs) are economically valuable, with biosynthesis linked to photosynthesis. NAD(P)H-quinone oxidoreductases (NDHs) play a crucial role in regulating photosynthetic processes. To better understand the functional roles and mechanisms of NDHs, we investigated Lavandula angustifolia NDHs (LaNDHs) using AlphaFold2 for structural prediction and RT-qPCR for expression analysis. Gene LaNDHs showed highest expression in leaves compared to other tissues (stems, roots and flowers), with upregulation under cadmium ion, heat, salt, and blue light. These findings suggest LaNDHs enhance stress tolerance and photosynthesis, offering potential for improving EO yield.